Pengaruh Kualitas Produk, E-Promotion dan Harga Terhadap Keputusan Pembelian Produk Fashion Pada Platform Shopee (Studi Pada Mahasiswa FEB Angkatan 2019 Universitas Islam Malang) - Oktaviani, Devi; Rachma, N.; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was carried out using a quantitative approach with a sample collection technique using a non-probability sampling method with a purposive sampling technique. Determination of the sample size of 100 respondents. Data analysis in this research uses the SPSS version 22 calculation tool. The results obtained from this research show that the independent variables simultaneously and partially have a positive and significant influence on purchasing decisions. Keywords: Product Quality, E-Promotion, Price, Purchase Decisions